High-Dose Dexmedetomidine for Severe Hyperactive Delirium Secondary to Intravenous Levetiracetam on Two Separate Occasions in the Same Patient. (2nd July 2022) - Ward, Chad; Khalid, Kiran; Rozette, Nicole
Abstract : We describe the case of a 5-year-old male who developed severe hyperactive delirium with aggressive violent behavior following the administration of IV levetiracetam for the treatment of status epilepticus on two occasions. The child's symptoms ranged from attacking his parents and the intensive care staff. Risperidone was given without any improvement in symptoms. A high-dose continuous infusion of IV dexmedetomidine was administered, and his violent behavior and delirium significantly improved. The two episodes of hyperactive delirium following IV levetiracetam administration occurred at ages 3 and 5, resulting in extensive work up including laboratory testing and cranial imaging, along with cerebral spinal fluid analysis and were normal. IV dexmedetomidine provided rapid symptom relief to prevent harm for the child, staff, and family on both occasions.